Reforma al art. 130 del Código de la Niñez Y Adolescencia vigente; respecto de excluir la obligación subsidiaria de la prestación del derecho de alimentos a las personas parento-filial de la tercera edad - Miguel Edgardo Escaleras Encarnación (2015)
The present research work, previous the obtaining of the degree of Lawyer of the Courts of the Republic in the majestic and solemn National University of Loja, entitled "REFORM TO THE ARTICLE 130 OF THE CURRENT CODE OF CHILDREN AND ADOLESCENTS, WITH RESPECT TO EXCLUDE OF THE SUBSIDIARY OBLIGATION OF PROVIDING THE RIGHT OF FOOD TO THE PARENTAL SENIOR BRANCH PEOPLE" was carried out in compliance with established project modality, as, it had for general objective, to design an adequate legal regulation relating to the payment of alimony by the subsidiary relatives framed into the old age, and then to propose a reform that will prevent continue committing misunderstandings acts like that are manifesting with the legal provisions established . This research work dedicates much of its development to address what constitutes and concerns to the administration of justice, especially for the reforms in the Code of Children and Adolescents, in which it is established that the maintenance payments be exempt to the subsidiary relatives seniors, aspect with realistic and positive sense, to put in evidence the valuable, right, wrong and also poor of our legal frame, with wide and democratic arguments. Through the present research work, I pretend to design legal rules to regulate this problem so prevalent in our society. In order to this legal reform proposed have the proper fundamentals, are studied topics, consistent with this problem, such as: The right of children in Ecuador, and a chronological analysis of the Rights of Children in the current legal framework, the Elderly legislation, the Human Rights that attending to children as elderly people, the Constitution, in which I analyze its principles, both, general and fundamental, and rights of freedom in the Code of Children and Adolescents , which analyzes the same, besides the legal basis for the constitutional reforms, more than a field investigation, to have present and to verify in a qualitative way the dimension of this problem